Manual Acupuncture Regulates Behavior and Cerebral Blood Flow in the SAMP8 Mouse Model of Alzheimer’s Disease - Ding, Ning; Jiang, Jing; Xu, Anping; Tang, Yinshan; Li, Zhigang (Frontiers in Neuroscience, 2019)
Background: A growing body of evidence has demonstrated that cerebrovascular function abnormality plays a key role in occurrence and worsening of Alzheimer’s disease (AD). Reduction of cerebral blood flow (CBF) is a sensitive marker to early perfusion deficiencies in AD. As one of the most important therapies in complementary and alternative medicine, manual acupuncture (MA) has been used in the treatment of AD. However, the moderating effect of MA on CBF remains largely unknown. Objective: To investigate the effect of MA on the behavior and CBF of SAMP8 mice. Methods: SAMP8 mice were randomly divided into the AD, MA, and medicine (M) groups, with SAMR1 mice used as the normal control (N) group. Mice in the M group were treated with donepezil hydrochloride at 0.65 μg/g. In the MA group, MA was applied at Baihui (GV20) and Yintang (GV29) for 20 min. The above treatments were administered once a day for 15 consecutive days. The Morris water maze and arterial spin labeling MRI were used to assess spatial learning and memory in behavior and CBF respectively. Results: Compared with the AD group, both MA and donepezil significantly decreased the escape latency (p< 0.01), while also elevating platform crossover number and the percentage of time and swimming distance in the platform quadrant (p< 0.01 or p< 0.05). The remarkable improvement in escape latency in the MA group appeared earlier than the M group, and no significant statistical significance was observed between the N and MA group with the exception of day 5 and 10. The CBF in the prefrontal lobe and hippocampus in the MA group was substantially higher than in the AD group (p< 0.05) with the exception of the right prefrontal lobe, with similar effects of donepezil. Conclusion: MA can effectively improve the spatial learning, relearning and memory abilities of SAMP8 mice. The increase in CBF in the prefrontal lobe and hippocampus could be an important mechanism for the beneficial cognitive effects of MA in AD.